Etnobotani ke atas tumbuhan yang digunakan sebagai ulam di Malaysia - Khairana Husain,; Mohd Shafie Zabidi,; Ibrahim Jantan,; Jamia Azdina Jamal,; Juriyati Jalil, (penerbit ukm, 2004)
This ethnobotanical survey is an effort to collect, identify and generate information on the variety of plants which are being utilized as salads by the Malays in Malaysia. The research was based on a literature survey and interviews carried out at the markets of Kuala Lumpur and downtown Port Dickson, Negeri Sembilan. A total of 109 species from 52 families had been successfully recorded to be consumed as salads. Of these, 47 species from 27 families are popular salads while 62 species from 38 families are traditional salads. Most of the salads are believed to possess a variety of medicinal values and are used to treat various diseases especially of a mild nature such as skin infections, digestion problems, mild pain, cut and ulcer, fever, cough and as anti-aging agents.